2018
DOI: 10.1002/jcp.26490
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐sensing receptor activates the NLRP3 inflammasome in LS14 preadipocytes mediated by ERK1/2 signaling

Abstract: The study of the mechanisms that trigger inflammation in adipose tissue is key to understanding and preventing the cardiometabolic consequences of obesity. We have proposed a model where activation of the G protein-coupled calcium sensing receptor (CaSR) leads to inflammation and dysfunction in adipose cells. Upon activation, CaSR can mediate the expression and secretion of proinflammatory factors in human preadipocytes, adipocytes, and adipose tissue explants. One possible pathway involved in CaSR-induced inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…CaSR is expressed in BMDNs, promotes the assembly of NLRP3 inflammasomes by regulating Ca 2+ concentration, and modulates the secretion and maturation of IL-1b (15). CaSR activates NLRP3 inflammasomes through the ERK1/2 signaling pathway in the preadipocyte line LS14 (16). However, the role of CaSR in UPEC-induced orchitis macrophages remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…CaSR is expressed in BMDNs, promotes the assembly of NLRP3 inflammasomes by regulating Ca 2+ concentration, and modulates the secretion and maturation of IL-1b (15). CaSR activates NLRP3 inflammasomes through the ERK1/2 signaling pathway in the preadipocyte line LS14 (16). However, the role of CaSR in UPEC-induced orchitis macrophages remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the mechanism through which CaSR modulates autophagy, we evaluated the ERK 1/2 pathway, given our previous reports of the relevance of this pathway in CaSR signaling in the human LS14 preadipocyte cell line [ 13 , 14 ]. We performed control experiments to assess ERK1/2 inhibition with the upstream (MEK1) ERK inhibitor U0126 in whole AT, primary in vitro differentiated adipocytes (not shown) and primary preadipocytes, observing ample variability and difficulty in obtaining good data in the first two and the best results in the latter.…”
Section: Resultsmentioning
confidence: 99%
“…This may reflect the well-described biased agonism of CaSR activation [ 11 , 12 , 46 ], which has been documented for polyamines toward ERK1/2 signaling in HEK293-CaSR cells [ 46 ]. Our previous reports showed that CaSR activation by cinacalcet triggers ERK1/2 pathway to regulate preadipocyte proliferation [ 13 ] and inflammasome activation [ 14 ]; however, this pathway probably does not mediate the effect on autophagy. The specific pathway involved in cinacalcet autophagy modulation remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in vitro experiments performed in LS14 preadipocytes proved that ERK1/2 signaling is involved in the cellular proliferation and NLRP3 activation induced by CaSR stimulation. 19 In the current study, we further evaluated whether the nuclear translocation of β-catenin is implicated in CaSRmediated collagen expression in CD cells treated with IL-1β. As the data show, we observed that the specific CaSR inhibitors (Calhex231, NPS2143, or CaSR siRNA) could partially attenuate the IL-1β-induced nuclear translocation of β-catenin in CD cells.…”
Section: Discussionmentioning
confidence: 99%